2014
DOI: 10.1111/jawr.12198
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Trends of Specific Conductance in Waters Discharged by Coal‐Mine Valley Fills in Central Appalachia, USA

Abstract: Anthropogenic salinization of freshwaters is a global concern. Coal surface mining causes release of dissolved sulfate, bicarbonate, calcium, magnesium, and other ions to surface waters in central Appalachia, USA, through practices that include mine rock disposal in valley fills (VFs). This region's surface waters naturally have low salinity, with specific conductance (SC, a salinity indicator) generally <200 lS/cm, and aquatic impacts have been found when SC exceeds the 300 to 500 lS/cm range. We analyzed SC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 34 publications
(69 reference statements)
1
35
1
Order By: Relevance
“…Evans et al (2014) demonstrated temporal decay of geologic influence on individual mine discharges, a finding that influenced our approach here. Bäthe and Coring (2011) and Coring and Bäthe (2011) reported declining mining-origin salinity over a 17-year period in Germany's River Table 4 Dissolved trace metals and other trace elements in the Powell River, 2000-2011, as concentrations and relative to CCC (estimated at 100 mg/L hardness); with statistically significant results of linear model testing for spatial (vs. river km) and temporal (vs. time) effects on the elements.…”
Section: Water Qualitymentioning
confidence: 95%
See 1 more Smart Citation
“…Evans et al (2014) demonstrated temporal decay of geologic influence on individual mine discharges, a finding that influenced our approach here. Bäthe and Coring (2011) and Coring and Bäthe (2011) reported declining mining-origin salinity over a 17-year period in Germany's River Table 4 Dissolved trace metals and other trace elements in the Powell River, 2000-2011, as concentrations and relative to CCC (estimated at 100 mg/L hardness); with statistically significant results of linear model testing for spatial (vs. river km) and temporal (vs. time) effects on the elements.…”
Section: Water Qualitymentioning
confidence: 95%
“…Peak and stabilized concentrations vary widely among spoil types (Orndorff et al, 2015). Evans et al (2014) analyzed SC over time for water outflows from 137 Virginia valley fills. The average peak concentration (1706 μS/cm), times required to reach that peak (9 years) and for decline to~500 μS/cm (~20 years), and an assumed 500 μS/cm stabilization level (Orndorff et al, 2015) were used to construct a temporal decay model for use in assessing water-quality impacts by mining-disturbed geologic materials (Fig.…”
Section: Miningmentioning
confidence: 99%
“…Mining operations move unweathered geologic materials into the ambient environment, where exposure to O 2 and H 2 O enables accelerated weathering and major ion release (Orndorff et al, 2015). Mining-origin elevated stream salinity and associated alterations of aquatic communities have been documented throughout Appalachian USA (Bernhardt et al, 2012;Cormier et al, 2013;Evans et al, 2014;Griffith et al, 2012;Hitt and Chambers, 2014;Pond et al, 2008;Timpano et al, 2015). The dominant major ions in mining-influenced Appalachian waters are generally SO 4 2À , HCO 3 À , Ca 2þ , and Mg 2þ ; but K þ , Na þ , and Cl À can also become elevated (Cormier et al, 2013;Pond et al, 2008;Timpano et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Both hydrologic and water quality changes are associated with Appalachian surface coal mining. Hydrologic changes include flashier stormwater runoff hydrographs with increased tailing (Guebert & Gardner, ; McCormick, Eshleman, Griffith, & Townsend, ; Messinger, ; Negley & Eshleman, ), increased volume and duration of baseflow (Green, Passmore, & Childers, ; Wiley, Evaldi, Eychaner, & Chambers, ; Messinger & Paybins, ; Zégre, Miller, Maxwell, & Lamont, ), and the formation of altered flow paths over and through the mined landscape (Evans, Zipper, Hester, & Schoenholtz, ; Miller & Zégre, ). These changes are brought about by decreases in evapotranspiration, surface compaction, and an increase in water storage (Zégre et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These approaches allow only limited understanding of flow regimes and essentially no understanding of the internal structure of valley fills and associated rock–water interactions that elevate TDS. Previous rock–water interaction studies at small scales have determined that initial leaching events produce high‐SC water and that SC of water produced by subsequent leaching typically declines with time and then stabilizes (Daniels et al, , ; Sena, Barton, Angel, Agouridis, & Warner, ; Evans et al, ; Orndorff et al, ). By contrast, integrative techniques that can gather spatially contiguous data regarding the storage, transport, and flow of water through spoil are needed to illuminate processes occurring within the valley fill (Miller & Zégre, ).…”
Section: Introductionmentioning
confidence: 99%